Chapter 1
Lookup tables for all problems in current book

1.1 section 1.0
1.2 section 2.0
1.3 section 3.0
1.4 section 4.0
1.5 section 5.0

1.1 section 1.0

Table 1.1: Lookup table

ID

problem

ODE

8713

1

\(y^{\prime } = \frac {\cos \left (y\right ) \sec \left (x \right )}{x}\)

8714

2

\(y^{\prime } = x \left (\cos \left (y\right )+y\right )\)

8715

3

\(y^{\prime } = \frac {\sec \left (x \right ) \left (\sin \left (y\right )+y\right )}{x}\)

8716

4

\(y^{\prime } = \left (5+\frac {\sec \left (x \right )}{x}\right ) \left (\sin \left (y\right )+y\right )\)

8717

5

\(y^{\prime } = y+1\)

8718

6

\(y^{\prime } = x +1\)

8719

7

\(y^{\prime } = x\)

8720

8

\(y^{\prime } = y\)

8721

9

\(y^{\prime } = 0\)

8722

10

\(y^{\prime } = 1+\frac {\sec \left (x \right )}{x}\)

8723

11

\(y^{\prime } = x +\frac {\sec \left (x \right ) y}{x}\)

8724

12

\(y^{\prime } = \frac {2 y}{x}\)

8725

13

\(y^{\prime } = \frac {2 y}{x}\)

8726

14

\(y^{\prime } = \frac {\ln \left (y^{2}+1\right )}{\ln \left (x^{2}+1\right )}\)

8727

15

\(y^{\prime } = \frac {1}{x}\)

8728

16

\(y^{\prime } = \frac {-x y-1}{4 x^{3} y-2 x^{2}}\)

8729

17

\(\frac {{y^{\prime }}^{2}}{4}-x y^{\prime }+y = 0\)

8730

18

\(y^{\prime } = \sqrt {\frac {y+1}{y^{2}}}\)

8731

19

\(y^{\prime } = \sqrt {1-x^{2}-y^{2}}\)

8732

20

\(y^{\prime }+\frac {y}{3} = \frac {\left (-2 x +1\right ) y^{4}}{3}\)

8733

21

\(y^{\prime } = \sqrt {y}+x\)

8734

23

\(x^{2} y^{\prime }+y^{2} = x y y^{\prime }\)

8735

24

\(y = x y^{\prime }+x^{2} {y^{\prime }}^{2}\)

8736

25

\(\left (x +y\right ) y^{\prime } = 0\)

8737

26

\(x y^{\prime } = 0\)

8738

27

\(\frac {y^{\prime }}{x +y} = 0\)

8739

28

\(\frac {y^{\prime }}{x} = 0\)

8740

29

\(y^{\prime } = 0\)

8741

30

\(y = x {y^{\prime }}^{2}+{y^{\prime }}^{2}\)

8742

31

\(y^{\prime } = \frac {5 x^{2}-x y+y^{2}}{x^{2}}\)

8743

32

\(2 t +3 x+\left (x+2\right ) x^{\prime } = 0\)

8744

33

\(y^{\prime } = \frac {1}{1-y}\)

8745

34

\(p^{\prime } = a p-b p^{2}\)

8746

35

\(y^{2}+\frac {2}{x}+2 x y y^{\prime } = 0\)

8747

36

\(x f^{\prime }-f = \frac {{f^{\prime }}^{2} \left (1-{f^{\prime }}^{\lambda }\right )^{2}}{\lambda ^{2}}\)

8748

37

\(x y^{\prime }-2 y+b y^{2} = c \,x^{4}\)

8749

38

\(x y^{\prime }-y+y^{2} = x^{{2}/{3}}\)

8750

39

\(u^{\prime }+u^{2} = \frac {1}{x^{{4}/{5}}}\)

8751

40

\(y^{\prime } y-y = x\)

8752

41

\(y^{\prime \prime }+2 y^{\prime }+y = 0\)

8753

41

\(5 y^{\prime \prime }+2 y^{\prime }+4 y = 0\)

8754

42

\(y^{\prime \prime }+y^{\prime }+4 y = 1\)

8755

43

\(y^{\prime \prime }+y^{\prime }+4 y = \sin \left (x \right )\)

8756

44

\(y = x {y^{\prime }}^{2}\)

8757

45

\(y^{\prime } y = 1-x {y^{\prime }}^{3}\)

8758

46

\(f^{\prime } = \frac {1}{f}\)

8759

47

\(t y^{\prime \prime }+4 y^{\prime } = t^{2}\)

8760

48

\(\left (t^{2}+9\right ) y^{\prime \prime }+2 y^{\prime } t = 0\)

8761

49

\(t^{2} y^{\prime \prime }-3 y^{\prime } t +5 y = 0\)

8762

50

\(t y^{\prime \prime }+y^{\prime } = 0\)

8763

51

\(t^{2} y^{\prime \prime }-2 y^{\prime } = 0\)

8764

52

\(y^{\prime \prime }+\frac {\left (t^{2}-1\right ) y^{\prime }}{t}+\frac {t^{2} y}{\left (1+{\mathrm e}^{\frac {t^{2}}{2}}\right )^{2}} = 0\)

8765

53

\(t y^{\prime \prime }-y^{\prime }+4 t^{3} y = 0\)

8766

54

\(y^{\prime \prime } = 0\)

8767

55

\(y^{\prime \prime } = 1\)

8768

56

\(y^{\prime \prime } = f \left (t \right )\)

8769

57

\(y^{\prime \prime } = k\)

8770

58

\(y^{\prime } = -4 \sin \left (x -y\right )-4\)

8771

59

\(y^{\prime }+\sin \left (x -y\right ) = 0\)

8772

60

\(y^{\prime \prime } = 4 \sin \left (x \right )-4\)

8773

61

\(y y^{\prime \prime } = 0\)

8774

62

\(y y^{\prime \prime } = 1\)

8775

63

\(y y^{\prime \prime } = x\)

8776

64

\(y^{2} y^{\prime \prime } = x\)

8777

65

\(y^{2} y^{\prime \prime } = 0\)

8778

66

\(3 y y^{\prime \prime } = \sin \left (x \right )\)

8779

67

\(3 y y^{\prime \prime }+y = 5\)

8780

68

\(a y y^{\prime \prime }+b y = c\)

8781

69

\(a y^{2} y^{\prime \prime }+b y^{2} = c\)

8782

70

\(a y y^{\prime \prime }+b y = 0\)

8783

71

\([x^{\prime }\left (t \right ) = 9 x \left (t \right )+4 y \left (t \right ), y^{\prime }\left (t \right ) = -6 x \left (t \right )-y \left (t \right ), z^{\prime }\left (t \right ) = 6 x \left (t \right )+4 y \left (t \right )+3 z \left (t \right )]\)

8784

72

\([x^{\prime }\left (t \right ) = x \left (t \right )-3 y \left (t \right ), y^{\prime }\left (t \right ) = 3 x \left (t \right )+7 y \left (t \right )]\)

8785

73

\([x^{\prime }\left (t \right ) = x \left (t \right )-2 y \left (t \right ), y^{\prime }\left (t \right ) = 2 x \left (t \right )+5 y \left (t \right )]\)

8786

74

\([x^{\prime }\left (t \right ) = 7 x \left (t \right )+y \left (t \right ), y^{\prime }\left (t \right ) = -4 x \left (t \right )+3 y \left (t \right )]\)

8787

75

\([x^{\prime }\left (t \right ) = x \left (t \right )+y \left (t \right ), y^{\prime }\left (t \right ) = y \left (t \right ), z^{\prime }\left (t \right ) = z \left (t \right )]\)

8788

76

\([x^{\prime }\left (t \right ) = 2 x \left (t \right )+y \left (t \right )-z \left (t \right ), y^{\prime }\left (t \right ) = -x \left (t \right )+2 z \left (t \right ), z^{\prime }\left (t \right ) = -x \left (t \right )-2 y \left (t \right )+4 z \left (t \right )]\)

8789

77

\(x^{\prime } = 4 A k \left (\frac {x}{A}\right )^{{3}/{4}}-3 k x\)

8790

78

\(\frac {y^{\prime } y}{1+\frac {\sqrt {1+{y^{\prime }}^{2}}}{2}} = -x\)

8791

78

\(\frac {y^{\prime } y}{1+\frac {\sqrt {1+{y^{\prime }}^{2}}}{2}} = -x\)

8792

79

\(y^{\prime } = \frac {y \left (1+\frac {a^{2} x}{\sqrt {a^{2} \left (x^{2}+1\right )}}\right )}{\sqrt {a^{2} \left (x^{2}+1\right )}}\)

8793

80

\(y^{\prime } = x^{2}+y^{2}\)

8794

81

\(y^{\prime } = 2 \sqrt {y}\)

8795

82

\(z^{\prime \prime }+3 z^{\prime }+2 z = 24 \,{\mathrm e}^{-3 t}-24 \,{\mathrm e}^{-4 t}\)

8796

83

\(y^{\prime } = \sqrt {1-y^{2}}\)

8797

84

\(y^{\prime } = x^{2}+y^{2}-1\)

8798

85

\(y^{\prime } = 2 y \left (x \sqrt {y}-1\right )\)

8799

86

\(y^{\prime \prime } = \frac {1}{y}-\frac {x y^{\prime }}{y^{2}}\)

8800

87

\(y^{\prime \prime }+y^{\prime }+y = 0\)

8801

88

\(y^{\prime \prime }+y^{\prime }+y = 0\)

8802

88

\(y^{\prime \prime }+y^{\prime }+y = 0\)

8803

89

\(y^{\prime \prime }-y^{\prime } y = 2 x\)

8804

90

\(y^{\prime }-y^{2}-x -x^{2} = 0\)

1.2 section 2.0

Table 1.3: Lookup table

ID

problem

ODE

8805

1

\(y^{\prime \prime }-x y^{\prime }-x y-x = 0\)

8806

2

\(y^{\prime \prime }-x y^{\prime }-x y-2 x = 0\)

8807

3

\(y^{\prime \prime }-x y^{\prime }-x y-3 x = 0\)

8808

4

\(y^{\prime \prime }-x y^{\prime }-x y-x^{2}-x = 0\)

8809

5

\(y^{\prime \prime }-x y^{\prime }-x y-x^{3}+2 = 0\)

8810

6

\(y^{\prime \prime }-x y^{\prime }-x y-x^{4}-6 = 0\)

8811

7

\(y^{\prime \prime }-x y^{\prime }-x y-x^{5}+24 = 0\)

8812

8

\(y^{\prime \prime }-x y^{\prime }-x y-x = 0\)

8813

9

\(y^{\prime \prime }-x y^{\prime }-x y-x^{2} = 0\)

8814

10

\(y^{\prime \prime }-x y^{\prime }-x y-x^{3} = 0\)

8815

11

\(y^{\prime \prime }-a x y^{\prime }-b x y-c x = 0\)

8816

12

\(y^{\prime \prime }-a x y^{\prime }-b x y-c \,x^{2} = 0\)

8817

13

\(y^{\prime \prime }-a x y^{\prime }-b x y-c \,x^{3} = 0\)

8818

14

\(y^{\prime \prime }-y^{\prime }-x y-x = 0\)

8819

15

\(y^{\prime \prime }-y^{\prime }-x y-x^{2} = 0\)

8820

16

\(y^{\prime \prime }-y^{\prime }-x y-x^{2}-1 = 0\)

8821

16

\(y^{\prime \prime }-y^{\prime }-x y-x^{2}-1 = 0\)

8822

17

\(y^{\prime \prime }-2 y^{\prime }-x y-x^{2}-2 = 0\)

8823

18

\(y^{\prime \prime }-4 y^{\prime }-x y-x^{2}-4 = 0\)

8824

19

\(y^{\prime \prime }-y^{\prime }-x y-x^{3}+1 = 0\)

8825

20

\(y^{\prime \prime }-2 y^{\prime }-x y-x^{3}-x^{2} = 0\)

8826

21

\(y^{\prime \prime }-y^{\prime }-x y-x^{3}+2 = 0\)

8827

22

\(y^{\prime \prime }-2 y^{\prime }-x y-x^{3}+2 = 0\)

8828

23

\(y^{\prime \prime }-4 y^{\prime }-x y-x^{3}+2 = 0\)

8829

24

\(y^{\prime \prime }-6 y^{\prime }-x y-x^{3}+2 = 0\)

8830

25

\(y^{\prime \prime }-8 y^{\prime }-x y-x^{3}+2 = 0\)

8831

26

\(y^{\prime \prime }-y^{\prime }-x y-x^{4}+3 = 0\)

8832

27

\(y^{\prime \prime }-y^{\prime }-x y-x^{3} = 0\)

8833

28

\(y^{\prime \prime }-x y-x^{3}+2 = 0\)

8834

29

\(y^{\prime \prime }-x y-x^{6}+64 = 0\)

8835

30

\(y^{\prime \prime }-x y-x = 0\)

8836

31

\(y^{\prime \prime }-x y-x^{2} = 0\)

8837

32

\(y^{\prime \prime }-x y-x^{3} = 0\)

8838

33

\(y^{\prime \prime }-x y-x^{6}-x^{3}+42 = 0\)

8839

34

\(y^{\prime \prime }-x^{2} y-x^{2} = 0\)

8840

35

\(y^{\prime \prime }-x^{2} y-x^{3} = 0\)

8841

36

\(y^{\prime \prime }-x^{2} y-x^{4} = 0\)

8842

37

\(y^{\prime \prime }-x^{2} y-x^{4}+2 = 0\)

8843

38

\(y^{\prime \prime }-2 x^{2} y-x^{4}+1 = 0\)

8844

39

\(y^{\prime \prime }-x^{3} y-x^{3} = 0\)

8845

40

\(y^{\prime \prime }-x^{3} y-x^{4} = 0\)

8846

41

\(y^{\prime \prime }-x^{2} y^{\prime }-x^{2} y-x^{2} = 0\)

8847

42

\(y^{\prime \prime }-x^{3} y^{\prime }-x^{3} y-x^{3} = 0\)

8848

43

\(y^{\prime \prime }-x y^{\prime }-x y-x = 0\)

8849

44

\(y^{\prime \prime }-x^{2} y^{\prime }-x y-x^{2} = 0\)

8850

45

\(y^{\prime \prime }-x^{2} y^{\prime }-x^{2} y-x^{3}-x^{2} = 0\)

8851

46

\(y^{\prime \prime }-x^{2} y^{\prime }-x^{3} y-x^{4}-x^{2} = 0\)

8852

47

\(y^{\prime \prime }-\frac {y^{\prime }}{x}-x y-x^{2}-\frac {1}{x} = 0\)

8853

48

\(y^{\prime \prime }-\frac {y^{\prime }}{x}-x^{2} y-x^{3}-\frac {1}{x} = 0\)

8854

49

\(y^{\prime \prime }-\frac {y^{\prime }}{x}-x^{3} y-x^{4}-\frac {1}{x} = 0\)

8855

50

\(y^{\prime \prime }-x^{3} y^{\prime }-x y-x^{3}-x^{2} = 0\)

8856

51

\(y^{\prime \prime }-x^{3} y^{\prime }-x^{2} y-x^{3} = 0\)

8857

52

\(y^{\prime \prime }-x^{3} y^{\prime }-x^{3} y-x^{4}-x^{3} = 0\)

8858

50

\(y^{\prime \prime \prime }-x^{3} y^{\prime }-x^{2} y-x^{3} = 0\)

1.3 section 3.0

Table 1.5: Lookup table

ID

problem

ODE

8859

1

\(y^{\prime \prime }+c y^{\prime }+k y = 0\)

8860

2

\(w^{\prime } = -\frac {1}{2}-\frac {\sqrt {1-12 w}}{2}\)

8861

3

\(y^{\prime \prime }+y = \sin \left (x \right )\)

8862

4

\(y^{\prime \prime }+y = \sin \left (x \right )\)

8863

5

\(y^{\prime \prime }+y = \sin \left (x \right )\)

8864

6

\(y^{\prime \prime }+y = \sin \left (x \right )\)

8865

7

\(y^{\prime \prime }+y = \sin \left (x \right )\)

8866

8

\(y^{\prime \prime }+y = \sin \left (x \right )\)

8867

9

\(y^{\prime \prime }+y = \sin \left (x \right )\)

8868

10

\(y^{\prime \prime }+y = \sin \left (x \right )\)

8869

11

\(y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right )\)

8870

12

\(y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right )\)

8871

13

\(y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right )\)

8872

14

\(y^{\prime \prime \prime }+y^{\prime }+y = x\)

8873

15

\(x^{4} y^{\prime \prime }+x^{3} y^{\prime }-4 x^{2} y = 1\)

8874

16

\(x^{4} y^{\prime \prime }+x^{3} y^{\prime }-4 x^{2} y = x\)

8875

17

\(x^{2} y^{\prime \prime }+x y^{\prime }-4 y = x\)

8876

18

\(x^{4} y^{\prime \prime \prime }+x^{3} y^{\prime \prime }+x^{2} y^{\prime }+x y = 0\)

8877

19

\(x^{4} y^{\prime \prime \prime }+x^{3} y^{\prime \prime }+x^{2} y^{\prime }+x y = x\)

8878

20

\(5 x^{5} y^{\prime \prime \prime \prime }+4 x^{4} y^{\prime \prime \prime }+x^{2} y^{\prime }+x y = 0\)

8879

21

\(\left (x^{2}+1\right ) y^{\prime \prime }+1+{y^{\prime }}^{2} = 0\)

8880

22

\(\left (x^{2}+1\right ) y^{\prime \prime }+1+{y^{\prime }}^{2} = x\)

8881

23

\(\left (x^{2}+1\right ) y^{\prime \prime }+1+x {y^{\prime }}^{2} = 1\)

8882

24

\(\left (x^{2}+1\right ) y^{\prime \prime }+y {y^{\prime }}^{2} = 0\)

8883

25

\(\left (x^{2}+1\right ) y^{\prime \prime }+{y^{\prime }}^{2} = 0\)

8884

26

\(y^{\prime \prime }+\sin \left (y\right ) {y^{\prime }}^{2} = 0\)

8885

27

\(\left (x^{2}+1\right ) y^{\prime \prime }+{y^{\prime }}^{3} = 0\)

8886

28

\(y^{\prime } = {\mathrm e}^{-\frac {y}{x}}\)

8887

29

\(y^{\prime } = 2 x^{2} \sin \left (\frac {y}{x}\right )^{2}+\frac {y}{x}\)

8888

30

\(4 x^{2} y^{\prime \prime }+y = 8 \sqrt {x}\, \left (\ln \left (x \right )+1\right )\)

8889

31

\(v v^{\prime } = \frac {2 v^{2}}{r^{3}}+\frac {\lambda r}{3}\)

1.4 section 4.0

Table 1.7: Lookup table

ID

problem

ODE

8890

1

\(2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = 0\)

8891

2

\(2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = 1\)

8892

3

\(2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = x +1\)

8893

4

\(2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = x\)

8894

5

\(2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = x^{2}+x +1\)

8895

6

\(2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = x^{2}\)

8896

7

\(2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = x^{2}+1\)

8897

8

\(2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = x^{4}\)

8898

9

\(2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = \sin \left (x \right )\)

8899

10

\(2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = 1+\sin \left (x \right )\)

8900

11

\(2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = x \sin \left (x \right )\)

8901

12

\(2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = \cos \left (x \right )+\sin \left (x \right )\)

8902

13

\(x^{2} y^{\prime \prime }+\left (\cos \left (x \right )-1\right ) y^{\prime }+y \,{\mathrm e}^{x} = 0\)

8903

14

\(\left (x -2\right ) y^{\prime \prime }+\frac {y^{\prime }}{x}+\left (x +1\right ) y = 0\)

8904

15

\(\left (x -2\right ) y^{\prime \prime }+\frac {y^{\prime }}{x}+\left (x +1\right ) y = 0\)

8905

16

\(\left (x +1\right ) \left (3 x -1\right ) y^{\prime \prime }+\cos \left (x \right ) y^{\prime }-3 x y = 0\)

8906

17

\(x y^{\prime \prime }+2 y^{\prime }+x y = 0\)

8907

18

\(2 x^{2} y^{\prime \prime }+3 x y^{\prime }-x y = x^{2}+2 x\)

8908

19

\(2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = 1\)

8909

20

\(2 x^{2} y^{\prime \prime }+2 x y^{\prime }-x y = 1\)

8910

21

\(y^{\prime \prime }+\left (x -6\right ) y = 0\)

8911

22

\(x^{2} y^{\prime \prime }+\left (3 x^{2}+2 x \right ) y^{\prime }-2 y = 0\)

8912

23

\(2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = x^{2}+\cos \left (x \right )\)

8913

24

\(2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = \cos \left (x \right )\)

8914

24

\(2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = x^{3}+\cos \left (x \right )\)

8915

24

\(2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = x^{3} \cos \left (x \right )\)

8916

24

\(2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = x^{3} \cos \left (x \right )+\sin \left (x \right )^{2}\)

8917

24

\(2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = \ln \left (x \right )\)

8918

25

\(2 x^{2} \left (x^{2}+x +1\right ) y^{\prime \prime }+x \left (11 x^{2}+11 x +9\right ) y^{\prime }+\left (7 x^{2}+10 x +6\right ) y = 0\)

8919

26

\(x^{2} \left (x +3\right ) y^{\prime \prime }+5 x \left (x +1\right ) y^{\prime }-\left (1-4 x \right ) y = 0\)

8920

27

\(x^{2} \left (-x^{2}+2\right ) y^{\prime \prime }-x \left (4 x^{2}+3\right ) y^{\prime }+\left (-2 x^{2}+2\right ) y = 0\)

8921

28

\({y^{\prime }}^{2}+y^{2} = \sec \left (x \right )^{4}\)

8922

29

\(\left (y-2 x y^{\prime }\right )^{2} = {y^{\prime }}^{3}\)

8923

31

\(x^{2} y^{\prime \prime }+y = 0\)

8924

32

\(x y^{\prime \prime }+y^{\prime }-y = 0\)

8925

33

\(4 x y^{\prime \prime }+2 y^{\prime }+y = 0\)

8926

34

\(x y^{\prime \prime }+y^{\prime }-y = 0\)

8927

35

\(x y^{\prime \prime }+\left (x +1\right ) y^{\prime }+2 y = 0\)

8928

36

\(x \left (x -1\right ) y^{\prime \prime }+3 x y^{\prime }+y = 0\)

8929

37

\(x^{2} \left (x^{2}-2 x +1\right ) y^{\prime \prime }-x \left (x +3\right ) y^{\prime }+\left (x +4\right ) y = 0\)

8930

38

\(2 x^{2} \left (x +2\right ) y^{\prime \prime }+5 x^{2} y^{\prime }+\left (x +1\right ) y = 0\)

8931

39

\(2 x^{2} y^{\prime \prime }+x y^{\prime }+\left (x -5\right ) y = 0\)

8932

40

\(2 x^{2} y^{\prime \prime }+2 x y^{\prime }-x y = \sin \left (x \right )\)

8933

41

\(2 x^{2} y^{\prime \prime }+2 x y^{\prime }-x y = x \sin \left (x \right )\)

8934

42

\(2 x^{2} y^{\prime \prime }+2 x y^{\prime }-x y = \cos \left (x \right ) \sin \left (x \right )\)

8935

43

\(2 x^{2} y^{\prime \prime }+2 x y^{\prime }-x y = x^{3}+x \sin \left (x \right )\)

8936

44

\(\cos \left (x \right ) y^{\prime \prime }+2 x y^{\prime }-x y = 0\)

8937

45

\(x^{2} y^{\prime \prime }+4 x y^{\prime }+\left (x^{2}+2\right ) y = 0\)

8938

46

\(x^{2} y^{\prime \prime }+x y^{\prime }-x y = 0\)

8939

47

\(x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0\)

8940

48

\(\left (x^{2}-x \right ) y^{\prime \prime }-x y^{\prime }+y = 0\)

8941

49

\(x^{2} y^{\prime \prime }+\left (x^{2}+6 x \right ) y^{\prime }+x y = 0\)

8942

50

\(x^{2} y^{\prime \prime }-x y^{\prime }+\left (x^{2}-8\right ) y = 0\)

8943

51

\(x^{2} y^{\prime \prime }-9 x y^{\prime }+25 y = 0\)

8944

52

\(x^{2} y^{\prime \prime }-x y^{\prime }-\left (x^{2}+\frac {5}{4}\right ) y = 0\)

8945

53

\(x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0\)

8946

54

\(x y^{\prime \prime }+\left (2-x \right ) y^{\prime }-y = 0\)

8947

55

\(2 x^{2} y^{\prime \prime }+3 x y^{\prime }-y = 0\)

8948

56

\(2 x^{2} y^{\prime \prime }+5 x y^{\prime }+4 y = 0\)

8949

57

\(x^{2} y^{\prime \prime }+3 x y^{\prime }+4 x^{4} y = 0\)

8950

58

\(x^{2} y^{\prime \prime }-x y = 0\)

8951

59

\(\left (-x^{2}+1\right ) y^{\prime \prime }+y^{\prime }+y = x \,{\mathrm e}^{x}\)

8952

60

\(y^{\prime } = y \left (1-y^{2}\right )\)

8953

61

\(\frac {x y^{\prime \prime }}{1-x}+y = \frac {1}{1-x}\)

8954

62

\(\frac {x y^{\prime \prime }}{1-x}+x y = 0\)

8955

63

\(\frac {x y^{\prime \prime }}{1-x}+y = \cos \left (x \right )\)

8956

64

\(\frac {x y^{\prime \prime }}{-x^{2}+1}+y = 0\)

8957

65

\(y^{\prime \prime } = \left (x^{2}+3\right ) y\)

8958

66

\(y^{\prime \prime }+\left (x -1\right ) y = 0\)

8959

67

\([x^{\prime }\left (t \right ) = x \left (t \right )+2 y \left (t \right )+2 t +1, y^{\prime }\left (t \right ) = 5 x \left (t \right )+y \left (t \right )+3 t -1]\)

8960

68

\(y^{\prime \prime }+20 y^{\prime }+500 y = 100000 \cos \left (100 x \right )\)

8961

69

\(y^{\prime \prime } \sin \left (2 x \right )^{2}+y^{\prime } \sin \left (4 x \right )-4 y = 0\)

1.5 section 5.0

Table 1.9: Lookup table

ID

problem

ODE

8962

1

\(y^{\prime \prime } = A y^{{2}/{3}}\)

8963

2

\(y^{\prime \prime }+2 x y^{\prime }+\left (x^{2}+1\right ) y = 0\)

8964

3

\(y^{\prime \prime }+2 \cot \left (x \right ) y^{\prime }-y = 0\)

8965

4

\(x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0\)

8966

5

\(4 x^{2} y^{\prime \prime }+\left (-8 x^{2}+4 x \right ) y^{\prime }+\left (4 x^{2}-4 x -1\right ) y = 4 \sqrt {x}\, {\mathrm e}^{x}\)

8967

6

\(x y^{\prime \prime }-\left (2 x +2\right ) y^{\prime }+\left (x +2\right ) y = 6 x^{3} {\mathrm e}^{x}\)

8968

7

\(y^{\prime }+y = \frac {1}{x}\)

8969

8

\(y^{\prime }+y = \frac {1}{x^{2}}\)

8970

9

\(x y^{\prime }+y = 0\)

8971

10

\(y^{\prime } = \frac {1}{x}\)

8972

11

\(y^{\prime \prime } = \frac {1}{x}\)

8973

12

\(y^{\prime \prime }+y^{\prime } = \frac {1}{x}\)

8974

13

\(y^{\prime \prime }+y = \frac {1}{x}\)

8975

14

\(y^{\prime \prime }+y^{\prime }+y = \frac {1}{x}\)

8976

15

\(h^{2}+\frac {2 a h}{\sqrt {1+{h^{\prime }}^{2}}} = b^{2}\)

8977

16

\(y^{\prime \prime }+2 y^{\prime }-24 y = 16-\left (x +2\right ) {\mathrm e}^{4 x}\)

8978

17

\(y^{\prime \prime }+3 y^{\prime }-4 y = 6 \,{\mathrm e}^{2 t -2}\)

8979

18

\(y^{\prime \prime }+y = {\mathrm e}^{a \cos \left (x \right )}\)

8980

19

\(y^{\prime } = \frac {y}{2 y \ln \left (y\right )+y-x}\)

8981

20

\(x y^{\prime \prime }-\left (2 x +1\right ) y^{\prime }+\left (x +1\right ) y = 0\)

8982

21

\(x^{2} y^{\prime }+{\mathrm e}^{-y} = 0\)

8983

22

\(y^{\prime \prime }+{\mathrm e}^{y} = 0\)

8984

23

\(y^{\prime } = \frac {x y+3 x -2 y+6}{x y-3 x -2 y+6}\)